Validation of Ab‐Initio‐Predicted Magnetic Anisotropies and Magneto‐structural Correlations in Linear Hetero‐trinuclear DyIII‐NiII2 Compounds. Issue 36 (19th May 2021) - Comba, Peter; Enders, Markus; Großhauser, Michael; Hiller, Markus; Klingeler, Rüdiger; Koo, Changhyun; Müller, Dennis; Rajaraman, Gopalan; Swain, Abinash; Tavhelidse, Msia; Wadepohl, Hubert
Abstract: Reported are single crystal SQUID and single crystal high‐frequency/high‐field EPR data of a trinuclear complex with a rare six‐coordinate coordination sphere of a Dy III center coupled to two terminal six‐coordinate Ni II ions. The analysis of the single crystal spectroscopic parameters allows for an accurate description of the ground state wavefunction. The experimental analysis is supplemented by the analysis of the paramagnetic NMR spectra, allowing for a thorough description of the Dy III center. The experimental data are interpreted on the basis of an ab initio ligand field analysis, and the computed parameters are in good agreement with the experimental observations. This supports the quality of the theoretical approach based on a pseudo‐spin Hamiltonian for the electronic ground state. Further support emerges from the ab initio ligand field theory based analysis of a structurally very similar system that, in contrast to the complex reported here, shows single molecule magnetic properties, and this is in agreement with the quantum‐chemical prediction and analysis. Abstract : Discussed is a linear trinuclear Dy III Ni II 2 complex with a rare hexacoordinate Dy III center. The magnetic properties were studied experimentally by single crystal SQUID magnetometry, single crystal high‐frequency/high‐field EPR and paramagnetic NMR spectroscopy. Parameters describing the ground state multiplet splitting have also been computed by ab‐initio quantum‐chemical calculations, and the large variety of experimental techniques allows for a thorough validation of the computational analysis.